ظاهرة إتلاف الكتب الإسلامية في الحضارة الإسلامية: The Phenomenon of Destruction of Islamic Books in the Islamic Civilization - Hammad, Hamza Abed Alkarim; Ali, Abdul Karim (Journal of Al-Tamaddun, 2023)
The Islamic civilization took a great interest in science and knowledge, including books that were vessels of knowledge from generation to generation, and this interest has appeared in many examples throughout history, but this interest was accompanied by deliberate destruction of Islamic books; so this research, which aims to identify the phenomenon of destruction of Islamic books in the Islamic civilization through the analysis of there was a deliberate destruction of books in the Islamic civilization, and attributed Researchers attribute this damage to: subjective, doctrinal and scientific reasons.